2014
DOI: 10.1177/0898264314551172
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships and Hypertension in Late Life

Abstract: Objectives Social relationships are widely understood to be important for sustaining and improving health and longevity, but it remains unclear how different dimensions of social relationships operate through similar or distinct mechanisms to affect biophysiological markers of aging-related disease over time. Methods This study utilized longitudinal data on a nationally representative sample of older adults from the National Social Life, Health, and Aging Project (2005 – 2011) to examine the prospective ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 64 publications
(107 reference statements)
2
27
1
2
Order By: Relevance
“…For instance, two meta-analytic reviews have reported that loneliness and poor social support are associated with higher mortality rates, and that the effect is comparable with some well-established risk factors such as obesity, physical inactivity, and smoking [ 5 , 6 ]. They are also predictive of development of coronary heart disease and stroke [ 7 ], increases in systolic blood pressure [ 8 , 9 ], and chronic pain [ 10 , 11 ] in longitudinal studies. The effect of loneliness on physical health may be via biological, psychological and/or behavioural mechanisms, including physiological functioning, neuroendocrine effects, gene effects, immune functioning, perception of stressful events, health behaviours and sleep quality [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two meta-analytic reviews have reported that loneliness and poor social support are associated with higher mortality rates, and that the effect is comparable with some well-established risk factors such as obesity, physical inactivity, and smoking [ 5 , 6 ]. They are also predictive of development of coronary heart disease and stroke [ 7 ], increases in systolic blood pressure [ 8 , 9 ], and chronic pain [ 10 , 11 ] in longitudinal studies. The effect of loneliness on physical health may be via biological, psychological and/or behavioural mechanisms, including physiological functioning, neuroendocrine effects, gene effects, immune functioning, perception of stressful events, health behaviours and sleep quality [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of both types of support is significant to one's health condition. As previous study, structural social support through social connectivity and the number of social ties is a necessary condition for improving health, because without social connections the functional aspect of social support is impossible (Y. C. Yang et al, 2015). However, above the presence of social connections, the functional dimensions of social support are also important, as our results indicate that part of the beneficial effect of having a social connection operates through how this relationship improves physiological functions and disease risks such as hypertension.…”
Section: Family As Primary Supportmentioning
confidence: 83%
“…Psychological, information, and instrumental support done daily are very helpful for the patient's own self and can also maintain self-esteem, sense of importance for others, and the perceived control over minor or impending obstacles and thus indirectly maintaining psychological wellbeing and (through positive influences) physical well-being as well (Thoits, 2011) Psychological and social aspects have a significant impact on the condition of hypertensive patients. Longitudinal studies revealed that people with higher levels of support had lower systolic blood pressure than those with lower support levels (Y. C. Yang, Boen, & Mullan Harris, 2015). Moreover, those with greater social support reported significantly lower perceived stress levels and depressive symptoms than those with less social support.…”
Section: Family As Primary Supportmentioning
confidence: 99%
“…Así mismo, es importante tener presente las diferencias entre las personas a nivel de metas, visión de sí mismo y los otros, así como los recursos personales, en las que se basan sus expectativas de resultado (Lazarus, 1999). Esto sin dejar de lado aspectos personales que tocan también la dimensión interpersonal, como el apoyo social ( Yang, Boen, y Mullan Harris, 2015).…”
Section: Factores Moderadores Y Mediadores De La Respuesta De Estrés unclassified